La Aracneida, Fernand Deligny y la tentativa de una filosofía gestual - Guerra-Miranda, Luis (Universidad Complutense de Madrid, 2023)
This article explores the work and thought of French pedagogue Fernand Deligny (1913-1996), focusing on his last project commonly referred to as the Tentative des Cévennes, developed between 1967-1996. From this experience that Deligny forged together with his collaborators, the article exposes the generation of a particular form of knowledge, a philosophy subordinated to a gestural solidarity network formed by human and non-human bodies, environments and situations, minimal gestures, everyday actions, and contingent events, visible only through a series of aesthetic devices that were developed during this period: writings, traces, maps, films, interviews, and wanderings. This gestural philosophy would be linked to a series of actions that would constitute an organic system in its apparent material dispersion. The article is organized through a biographical and historical contextualization, to later deploy the theoretical framework of the research and a conclusion.
Keywords: Ranska; estetiikka